The overlook: [compact disc, unabridged] : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series., 2007)
LAPD detective Harry Bosch is called to investigate the execution-style murder of Dr. Stanley Kent, who had no apparent ties to organized crime but had access to dangerous radioactive substances. What begins as a routine homicide investigation opens up into something much larger, more dangerous, and more urgent.